The role of archival aerial photography in shaping our understanding of the funerary landscape of hellenistic and Roman Cyprus - Lysandrou, Vasiliki; Agapiou, Athos (My University, 2020)
This study deals with the investigation of the Eastern necropolis of Nea Paphos in western Cyprus, employing archival and recent aerial photographs for the identification of surface/near-surface ancient architectural remains. The analysis of the primary archival aerial photograph employed for this study reveals the archaeological visibility of the site as it had been captured approximately 15 years before its rescue excavation in the 1980s. The outcomes from the enhancement and interpretation of the archival aerial photograph supplement known archaeological information of the area and elucidate the understanding of the spatial distribution of the tombs as well as the geographic extent of the necropolis.
Keywords: Eastern necropolis of Nea Paphos; Aerial investigation; Archive aerial datasets; Architectural feature detection; Hellenistic and Roman Cyprus